2001
DOI: 10.1074/jbc.m106688200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p21WAF1/Cip1 Transcription through Sp1 Sites by Histone Deacetylase Inhibitor Apicidin

Abstract: We previously reported that apicidin, a novel histone deacetylase inhibitor, inhibited the proliferation of tumor cells via induction of p21 WAF1/Cip1 . In this study, we determined the molecular mechanisms by which apicidin induced the p21 WAF1/Cip1 gene expression in HeLa cells. Apicidin induced p21 WAF1/Cip1 mRNA independent of the de novo protein synthesis and activated the p21 WAF1/Cip1 promoter through Sp1-3 site located at ؊82 and ؊77 relative to the transcription start site. This transcriptional activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 35 publications
8
76
1
Order By: Relevance
“…HDAC4 represses p21 WAF1/Cip1 in cancer cells in vitro in a Sp1-dependent manner Although most reports demonstrated that HDAC inhibitors induced p21 WAF1/Cip1 expression in an Sp1/Sp3-dependent manner Sowa et al, 1997Sowa et al, , 1999Han et al, 2001;Wilson et al, 2006), a role for p53 in HDAC-associated p21 WAF1/Cip1 expression has also been reported in several human cancer cell lines (Lagger et al, 2003;Luo et al, 2004;Roy et al, 2005;Zhao et al, 2006).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…HDAC4 represses p21 WAF1/Cip1 in cancer cells in vitro in a Sp1-dependent manner Although most reports demonstrated that HDAC inhibitors induced p21 WAF1/Cip1 expression in an Sp1/Sp3-dependent manner Sowa et al, 1997Sowa et al, , 1999Han et al, 2001;Wilson et al, 2006), a role for p53 in HDAC-associated p21 WAF1/Cip1 expression has also been reported in several human cancer cell lines (Lagger et al, 2003;Luo et al, 2004;Roy et al, 2005;Zhao et al, 2006).…”
Section: Resultsmentioning
confidence: 96%
“…Epigenetic suppression of p21 WAF1/Cip1 is directly linked to HDAC activity, as inhibition of HDAC activities in cancer cells induces transcriptional reactivation of p21 WAF1/Cip1 through hyperacetylation of histones H3 and H4 in the proximal promoter region Richon et al, 2000;Sawa et al, 2004). In other studies, p21 Waf1/Cip1 induction by HDAC inhibitors was mediated through Sp1 sites through Sp1 family transcription factors, Sp1 and/or Sp3 Sowa et al, 1997Sowa et al, , 1999Han et al, 2001;Wilson et al, 2006). To date, the most common model for p21 WAF1/Cip1 repression in cancer cells is the recruitment of HDACs by Sp1/-Sp3 transcription factors in the proximal promoter region encompassing the Sp1/Sp3 binding sites, which in turn repress p21 WAF1/Cip1 transcription by deacetylating histones H3 and H4.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, it has been shown that the transcriptional activation of p21 WAF1/Cip1 by apicidin is dependent on protein kinase C (PKCs) as indicated by studies of the PKC inhibitor (Han et al, 2001). However, which of the PKC isoforms was involved in p21 WAF1/Cip1 gene expression by apicidin or upstream signaling events that leads to PKC activation are not yet clear.…”
Section: Introductionmentioning
confidence: 98%
“…Recent evidence suggests that the induction of p21 WAF1/Cip1 by these stimuli could be regulated by various signal transduction pathways that mediate cell growth, differentiation, and stress response (Hu et al, 1999;Lee et al, 2000;Mitsuuchi et al, 2000). Also, it has been demonstrated that p21 WAF1/Cip1 induction by HDAC inhibitors was mediated via Sp1 sites through Sp1 family transcription factors, Sp1 and/or Sp3 (Nakano et al, 1997;Sowa et al, 1999;Huang et al, 2000;Han et al, 2001). However, the detailed signal transduction pathways involved in p21 WAF1/Cip1 gene regulation by HDAC inhibitors still remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%